ANALISIS PERAN KOMUNIKASI.ORGANISASI INTERNAL DAN EKSTERNAL PADA KELURAHAN MUSTIKASARI - BEKASI - TRISNAWATI KUSUMAWARDHANI (Interpretasi: Communication & Public Relations, 2021)
Good organizational communication is communication carried out by an organization both internally and externally. Internal organizational communication is communication carried out within an organization where there is only communication between members of the organization. External organizational communication is communication carried out by an organization with its potential partners, prospective clients, partners and clients, and the surrounding community. Kelurahan Mustikasari- Bekasi in carrying out its organizational structure has carried out good internal and external organizational communication. In organizational communication also includes interpersonal communication / interpersonal. Kelurahan Mustikasari is part of Mustikajaya Subdistrict, two among the other Kelurahans are Kelurahan Cimuning and Kelurahan Pedurenan. Good internal and external organizational communication links show that the leadership of the organization desires to realize the vision, mission, and goals of the organization.